2018
DOI: 10.1080/09537104.2018.1542122
|View full text |Cite
|
Sign up to set email alerts
|

Increased platelet reactivity and platelet–leukocyte aggregation after elective coronary bypass surgery

Abstract: Inflammatory mechanisms are activated, and thrombotic complications occur during the initial months after coronary artery bypass grafting (CABG). Therefore, changes over time of platelet activation and platelet-leukocyte interactions after CABG are of interest. Whole-blood flow cytometry was performed before, and 4-6 days, one month, and three months after elective CABG in 54 men with stable coronary artery disease treated with acetylsalicylic acid (ASA). Single platelets and platelet-leukocyte aggregates (PLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 36 publications
2
18
0
2
Order By: Relevance
“…2 The results revealed that P-selectin expression was significantly increased (P < .005) from 1 to 3 months. 3 This finding strongly suggests that the contact of medical devices with blood can continuously increase platelet reactivity. Thus, activated platelets may contribute to the increased risk of thrombus formation due to the insertion of medical devices such as CVCs.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…2 The results revealed that P-selectin expression was significantly increased (P < .005) from 1 to 3 months. 3 This finding strongly suggests that the contact of medical devices with blood can continuously increase platelet reactivity. Thus, activated platelets may contribute to the increased risk of thrombus formation due to the insertion of medical devices such as CVCs.…”
Section: Discussionmentioning
confidence: 95%
“…Another study investigated platelet activation by evaluating CD62P after 4‐6 days, 1 and 3 months of myocardial revascularization surgery . The results revealed that P‐selectin expression was significantly increased ( P < .005) from 1 to 3 months . This finding strongly suggests that the contact of medical devices with blood can continuously increase platelet reactivity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations